Joaquim Pintassilgo: trajectory, thought, and contributions to the history of education. (Revista Lusófona de Educação, 2025)
This paper presents an interview with Joaquim Pintassilgo, Professor of History of Education at the University of Lisbon, whose academic trajectory has significantly contributed to the understanding of educational transformations in Portugal. The interview addresses the issue of the relationship between the state and alternative forms of schooling in the Portuguese context. The main objective was to discuss, in light of his intellectual production, the tensions between the public and private spheres in the history of education, as well as the contemporary meanings of public school deregulation. The methodology involved the development of an interview script based on a bibliographic review of the author's work, mapped through Google Scholar from 1996 to 2025. The conversation covered topics such as his academic background, political activism, teaching career, the Portuguese Modern School movement, and education regulation policies. The analysis focused particularly on his article The public and the private in the history of education: The example of Portugal (second half of the 19th century – early 20th century), published in 2011. In conclusion, the interview highlighted the importance of a critical and historically grounded approach to educational processes, as well as the recognition of innovative and cooperative experiences in the field of education.